2013
DOI: 10.1016/j.echo.2013.03.018
|View full text |Cite
|
Sign up to set email alerts
|

Frequent Periodic Leg Movement during Sleep Is Associated with Left Ventricular Hypertrophy and Adverse Cardiovascular Outcomes

Abstract: Background Sleep disturbance caused by obstructive sleep apnea is recognized as a contributing factor to adverse cardiovascular outcomes. However, the effect of restless legs syndrome (RLS), another common cause of fragmented sleep, on cardiac structure, function and long-term outcomes is not known. We assessed the effect of frequent leg movement during sleep on cardiac structure and outcomes in patients with RLS. Methods In our retrospective study, RLS patients referred for polysomnography were divided into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
63
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(66 citation statements)
references
References 47 publications
1
63
0
1
Order By: Relevance
“…PLMS severity was reported to be associated with high mortality in patients with end-stage renal disease [44]. In addition, our group has reported that HD patients with severe PLMS were found to exhibit significant alternations in cardiac structure [45], which has been also confirmed in patients with idiopathic RLS [46]. Interestingly, in this previous study [45], the severity of RLS, in contrast to the severity of PLMS, was not related to structural cardiac abnormalities.…”
Section: Page 12 Of 35mentioning
confidence: 45%
“…PLMS severity was reported to be associated with high mortality in patients with end-stage renal disease [44]. In addition, our group has reported that HD patients with severe PLMS were found to exhibit significant alternations in cardiac structure [45], which has been also confirmed in patients with idiopathic RLS [46]. Interestingly, in this previous study [45], the severity of RLS, in contrast to the severity of PLMS, was not related to structural cardiac abnormalities.…”
Section: Page 12 Of 35mentioning
confidence: 45%
“…6,23,96,97 However, a large study did not find association with RLS and mortality, 98 and some studies showed increased mortality in females but not in males. 99,100 Studies of mortality and RLS/ PLMS have been limited by a small number of patients, epidemiological/cross-sectional designs, short follow-up period, and different definitions to classify RLS/PLMS patients.…”
Section: Association Between Rls/plms and Mortalitymentioning
confidence: 99%
“…The ejection fraction (EF) was not different between the groups. 6 A study of 23 men with severe, stable CHF (all with EF <35%) and 9 healthy controls found that 52% of CHF patients have a PLMI >25/h. Of those, one-third had a PLMI >50/h, compared with control …”
Section: Rls/plms and Arrhythmiasmentioning
confidence: 99%
“…There is no abnormal sensation in the extremities, unless PLMS is complicated by RLS. High-frequency PLM may be associated with left ventricular hypertrophy and incident HF 31) , through an increase in SNA in association with PLMS-related arousals.…”
Section: B) Sleep-disordered Breathing (Sdb)mentioning
confidence: 99%